ML-16 First clinical experience of administration of Tirabrutinib for the patients with newly diagnosed primary central nervous system lymphoma. (6th December 2021) - Onodera, Sho; Akimoto, Jiro
Abstract: Tirabrutinib (TIR), a Burton's tyrosine kinase inhibitory drug, has been approved in Japan for treating relapsed/refractory primary central nervous system lymphoma (PCNSL). The authors recently encountered three patients with newly diagnosed refractory PCNSL using TIR. Three patients, 48, 78 and 88 years-old males, diagnosed with PCNSL by histologically verification were firstly treated with high dose Methotrexate based chemotherapy (HD-MTX) and/or radiotherapy, however these cases were refractory for these standard treatments, demonstrated early cerebrospinal fluid dissemination or accompanied with severe adverse event. The authors decided to administrate TIR to these patients with a full informed consent. TIR demonstrated dramatic reduction of the volume of tumor on MRI within one month after administration of TIR, and improved the patient's performance status. However, one case demonstrated liver dysfunction and multiple brain abscess due to aspergillus infection, and one case demonstrated early progression of the tumor 49 days after starting TIR. Administration of TIR for the patients with newly diagnosed refractory PCNSL demonstrated a rapid and dramatic clinical response, and presented with several clinical implications for this complicated condition.